Central and obstructive apneas prevalence in heart failure with reduced, mid-range and preserved ejection fraction. (25th November 2020) - Borrelli, C; Sciarrone, P; Gentile, F; Ghionzoli, N; Mirizzi, G; Passino, C; Emdin, M; Giannoni, A
Abstract: Background: Central apneas (CA) and obstructive apneas (OA) are highly prevalent in heart failure (HF) both with reduced and preserved systolic function. However, a comprehensive evaluation of apnea prevalence across HF according to ejection fraction (i.e HF with patients with reduced, mid-range and preserved ejection fraction- HFrEf, HFmrEF and HFpEF, respectively) throughout the 24 hours has never been done before. Materials and methods: 700 HF patients were prospectively enrolled and then divided according to left ventricular EF (408 HFrEF, 117 HFmrEF, 175 HFpEF). All patients underwent a thorough evaluation including: 2D echocardiography; 24-h Holter-ECG monitoring; cardiopulmonary exercise testing; neuro-hormonal assessment and 24-h cardiorespiratory monitoring. Results: In the whole population, prevalence of normal breathing (NB), CA and OA at daytime was 40%, 51%, and 9%, respectively, while at nighttime 15%, 55%, and 30%, respectively. When stratified according to left ventricular EF, CA prevalence decreased from HFrEF to HFmrEF and HFpEF: (daytime CA: 57% vs. 43% vs. 42%, respectively, p=0.001; nighttime CA: 66% vs. 48% vs. 34%, respectively, p<0.0001), while OA prevalence increased (daytime OA: 5% vs. 8% vs. 18%, respectively, p<0.0001; nighttime OA: 20 vs. 29 vs. 53%, respectively, p<0.0001). When assessing moderte-severe apneas, defined with an apnea/hypopnea index >15 events/hour, prevalence of CA was again higher in HFrEF than HFmrEF and HFpEF both at daytime (daytime moderate-severe CA: 28% vs. 19% and 23%, respectively, p<0.05) and at nighttime (nighttime moderate-severe CA: 50% vs. 39% and 28%, respectively, p<0.05). Conversely, moderate-severe OA decreased from HFrEF to HFmrEF to HFpEF both at daytime (daytime moderate-severe OA: 1% vs. 3% and 8%, respectively, p<0.05) and nighttime (noghttime moderate-severe OA: 10% vs. 11% and 30%, respectively, p<0.05). Conclusions: Daytime and nighttime apneas, both central and obstructive in nature, are highly prevalent in HF regardless of EF. Across the whole spectrum of HF, CA prevalence increases and OA decreases as left ventricular systolic dysfunction progresses, both during daytime and nighttime. Funding Acknowledgement: Type of funding source: None